Proposed basic timetables for expedited arbitration. (9th January 2023) - Webster, Tom
Abstract: This article sets out two basic procedural timetables for the hearing of arbitration within 6 months after the constitution of the Tribunal and rendering of an award within 30 days thereafter. Two of the key complaints about international arbitration relate to time and costs. In the author's view, these can be addressed by moving away from what have become the default timetables for international commercial arbitration. In this respect, the most obvious issue is the 2-month documentary production period. However, that is not the only issue, and documentary production has a role in arbitration. Another issue relates to expert evidence. A further issue relates to defining the issues and having input from the Tribunal regarding the issues prior to the evidentiary hearing. Yet another issue relates to the conduct of the evidentiary hearing itself. And a final issue is the time to finalize the Award. These expedited procedural timetables are based on the adversarial rather than the inquisitorial approach, although with the active participation of the Tribunal in the evidentiary hearing. They are intended to be used for mid-sized or larger arbitrations with a three-member Tribunal, although they could be used for smaller arbitrations or with a Sole Arbitrator.